Material Balances under Uncertainty - Weitzman, Martin L. (Quarterly Journal of Economics, 1971)
I. Introduction, 262. — II. The economic environment, 263. — III. Mechanics of planning, 265. — IV. Material reserves, 266. — V. Plan formulation and material balances. 267. — VI. Effects of uncertainty, 268. — VII. Plan execution and the costs of incorrect planning, 270. — VIII. Short- and long-term plans, 272. — IX. Optimal planning and dynamics programming, 273. — X. Sensitivity analysis, 276. — XI. Concluding remarks, 278. — Appendix: Proof of the form of an optimal policy, 278.